Quercetin enhances survival and axonal regeneration of motoneurons after spinal root avulsion and reimplantation: experiments in a rat model of brachial plexus avulsion - Yanfeng Huang; Xie Zhang; Qionghui Huang; Yaoxing Dou; Chang Qu; Qingqing Xu; Qiuju Yuan; Yan-Fang Xian; Zhi-Xiu Lin (BMC, 2022)
Highlights • Quercetin (QCN) promotes motoneuron survival and accelerates axonal regeneration after brachial plexus root avulsion/re-implantation in rats. • QCN improves motor function recovery of the forelimb. • QCN exhibits neuroprotective effects via inhibiting neuroinflammation and upregulating the neurotrophins. • QCN alleviates the avulsion-induced oxidative damage in rats. • QCN inhibits the avulsion-induced neuronal apoptosis in rats. • QCN modulates Nrf2/HO-1 and neurotrophin/Akt/MAPK signaling pathways.